Vaccine Coverage in Children Younger Than 1 Year of Age during Periods of High Epidemiological Risk: Are We Preparing for New Outbreaks? - Valeria Herdea; Raluca Ghionaru; Claudiu N. Lungu; Eugene Leibovitz; Smaranda Diaconescu (MDPI AG, 2022)
Background: According to WHO, infectious disease control can be achieved if the vaccine coverage (VC) exceeds 90%. In recent years there has been a declining trend in VC which could lead to the recurrence of infectious diseases. Objectives: The study analyzed the determinants of VC and of parental decisions regarding immunization in children aged 0-1 year monitored during two high-risk epidemiological periods (the measles epidemic and the COVID-19 pandemic period). Methods: A retrospective observational cohort study-data regarding vaccination of children younger than 1 year of age during the periods January 2019-June 2019 (measles epidemic) and January 2020-June 2020 (COVID-19 pandemic) were analyzed. 2.850 children from 2019 and 2.823 children from 2020 were enrolled. Family physicians interacted with 2840 parents or legal guardians in 2019 and with 2800 parents or legal guardians in 2020, during the infants' consults providing medical information and answer to their questions and worries regarding their immunization. Data on immunization schedules on the determinants of parents' decisions regarding vaccination were evaluated. Results: During 2019-2020, VC has followed a declining trend for each type of vaccine included in the Romanian National Immunization Program; the most affected were infants aged 9-12 months during both periods: in 9-month aged infants, the MMR vaccine VC was 67.49% in 2019 vs. 59.04% in 2020 (p < 0.004). In the 12 months aged infants, the MMR VC was 64.29% in 2019 vs. 55.88% in 2020 (p < 0.005). For the Hexavalent vaccine administered at the age of 11 months, the VC was 71.59% in 2019 vs. 62.08% in 2020 (p < 0.001). The determinants of parents' decisions regarding vaccination included parental hesitance 2019-25% vs. 2020-35%, fear on side effects 2019-32% vs. 2020-45%, vaccination denial 2019-7% vs. 2020-10%. Conclusion: We found a declining trend in the VC in Romania during the epidemic and pandemic periods. The decrease in VC for MMR generated a major risk for new measles outbreaks Permanent awareness educational campaigns regarding infectious disease risk are needed, accompanied by the empowerment of primary care and the emergence of an immunization management program based on national regulatory legislation.